(untitled) (Transport systems and technologies, 2018)
The article is devoted to risk assessment in enterprises on repair cars. Modern production is complex, from the point view ensuring the reliability systems. A feature of their operation is how a large amount of initial data to start the process (human resources, technological resources, material resources), and a large number of consequences failures in the system (the failure of the repairs within the specified time, failure of production volumes, material losses). This leads to the necessity assessing not only the possible failures of the production system but also determine the degree risk of different unwanted events. To formalize the cause-and-effect relationships that determine the appearance of different kinds of failures in the production system may use procedural mechanisms – ‘Analysis types, consequences and criticality of failures’. The creation of a risk management system based on advanced mathematical methods and engineering approaches that will significantly reduce losses in the production system and to provide a given level reliability of production processes.